My Unknown Soldier - Kryvenko, Anna (Czech Republic ; Slovakia ; Latvia, 2018)
A documentary composed of archival footage from the 1968 occupation of Czechoslovakia by the Warsaw Pact armies, told from the perspective of the occupier - the titular unknown soldier.
Verzio Film Festival Submission
Keywords: Documentary films